(untitled) (TAJ: Journal of Teachers Association, 2018)
Breast cancer is one of the most common types of cancer, making up about 25% of all cancer. Despite the high incidence rates, in Western countries, 89% of women diagnosed with breast cancer are still alive 5 years after their diagnosis, which is due to proper detection and treatment. Mainly there are several types of breast cancer. One of the classes is determined by the expression of proteins or receptor and genes. Breast cancer cells may or may not have many different types of receptors, the three most important in the present classification being: estrogen receptor (ER), progesterone receptor (PR), and HER2/neuHER2/neu (human epidermal growth factor receptor 2) receptors. Cells with or without these receptors are called ER positive (ER+), ER negative (ER-), PR positive (PR+), PR negative (PR-), HER2 positive (HER2+), and HER2 negative (HER2-). Cells with negative receptors are called triple negative. Around 25% to 30% of breast cancers show amplification of the HER2 gene. Trastuzumab is a humanized monoclonal antibody targeting the extracellular domain of HER2 receptor. In the metastatic breast cancer setting, Trastuzumab significantly improves overall survival, and is responsible for a change in the natural course of this disease. In this study we have gone to assess the outcome of HER2 positive breast cancer patients with trastuzumab along with cytotoxic chemotherapy in comparison to the conventional chemotherapy. All tumours were tested for HER2/neu status. A randomized control trial was run with 130 patients having HER2 positive breast cancer in Rajshahi Medical College Hospital and different private hospitals and clinics of Rajshahi city in this study. TAJ 2017; 30(1): 30-35